Understanding the reactivity of CoCrMo-implant wear particles - Koronfel,MA; Goode,AE; Weker,JN; Tay,SER; Stitt,CA; Simoes,TA; Mosselmans,JFW; Quinn,P; Brydson,R; Hart,A; Toney,MF; Porter,AE; et al. (npj Materials Degradation, 2018)
CoCrMo-based metal-on-metal hip implants experienced unexpectedly high failure rates despite the high wear and corrosion resistance of the bulk material. Although they exhibit a lower volumetric wear compared to other implant materials, CoCrMo-based implants produced a significantly larger 'number' of smaller wear particles. CoCrMo is nominally an extremely stable material with high Cr content providing passivity. However, despite the Co:Cr ratio in the original alloy being 2:1; chemical analyses of wear particles from periprosthetic tissue have found the particles to be composed predominately of Cr species, with only trace amounts of Co remaining. Here a correlative spectroscopy and microscopy approach has shown that these particles dissolve via a non-stoichiometric, and geometrically inhomogeneous, mechanism similar to de-alloying. This mechanism is previously unreported for this material and was not apparent in any of the regulatory required tests, suggesting that such tests are insufficiently discriminating.